(untitled) (Economic and Political Thought, 2020)
The aim of this paper is to present the structure of Poland’s trade with its main partners in 2015–2020. We argue that the geographical diversity of Polish trade – a positive balance with the EU countries and a negative one with other countries – results from the structure of imports and exports. In turn, this structure depends on the category of commodity being traded in. Another important factor in the context of the economic order is the ease of doing business. However, the global economy, including the EU, has been severely affected by the coronavirus pandemic outbreak, which also has had its impact on the Polish market: we can observe a significant weakening of Polish foreign trade in the first quarter of 2020. In the first part of the paper, we analyse Poland’s foreign trade in the period 2015–2020. Going into detail, we discuss the diversification of trade with regard to Poland’s major trading partners. For many years, Germany, the Czech Republic and the United Kingdom have been Poland’s main export partners. The categories of commodities that Poland trades in are recognised as the main cause of the disproportion in the trade balance. Poland has been achieving good export results due to the successively increasing geographical diversification of the directions of Polish trade expansion.